PEX13 deficiency in mouse brain as a model of Zellweger syndrome: abnormal cerebellum formation, reactive gliosis and oxidative stress - C. Catharina Müller; Tam H. Nguyen; Barbara Ahlemeyer; Mallika Meshram; Nishreen Santrampurwala; Siyu Cao; Peter Sharp; Pamela B. Fietz; Eveline Baumgart-Vogt; Denis I. Crane (The Company of Biologists, 2011)
SUMMARY Delayed cerebellar development is a hallmark of Zellweger syndrome (ZS), a severe neonatal neurodegenerative disorder. ZS is caused by mutations in PEX genes, such as PEX13, which encodes a protein required for import of proteins into the peroxisome. The molecular basis of ZS pathogenesis is not known. We have created a conditional mouse mutant with brain-restricted deficiency of PEX13 that exhibits cerebellar morphological defects. PEX13 brain mutants survive into the postnatal period, with the majority dying by 35 days, and with survival inversely related to litter size and weaning body weight. The impact on peroxisomal metabolism in the mutant brain is mixed: plasmalogen content is reduced, but very-long-chain fatty acids are normal. PEX13 brain mutants exhibit defects in reflex and motor development that correlate with impaired cerebellar fissure and cortical layer formation, granule cell migration and Purkinje cell layer development. Astrogliosis and microgliosis are prominent features of the mutant cerebellum. At the molecular level, cultured cerebellar neurons from E19 PEX13-null mice exhibit elevated levels of reactive oxygen species and mitochondrial superoxide dismutase-2 (MnSOD), and show enhanced apoptosis together with mitochondrial dysfunction. PEX13 brain mutants show increased levels of MnSOD in cerebellum. Our findings suggest that PEX13 deficiency leads to mitochondria-mediated oxidative stress, neuronal cell death and impairment of cerebellar development. Thus, PEX13-deficient mice provide a valuable animal model for investigating the molecular basis and treatment of ZS cerebellar pathology.